Biometry and Storage Ability at 4°C of Slaughtered Buck Testis and Correlations of Various Epididymal Seminal Attributes - Patel, Rajesh Pratap; Singh, Bhoopendra; Kumar, Rajesh; Srivastava, Sushant (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The present study was conducted on 48 pairs of fresh testicles obtained from mature bucks, irrespective of breed, slaughtered at localabattoir and AL-Nafees Proteins Pvt. Ltd., Mewat, Haryana. Various testicular and epididymal biometric parameters, epididymal seminalattributes and correlation coefficients between testicular volume and seminal epididymal attributes were studied. The testicles withepididymis were put randomly into six groups (plastic bags) each of eight pairs and were stored at 4°C for 96 hours in a refrigerator. Onebag/group each was taken out at 6, 12, 24, 48, 72, and 96 hours of cold storage to study the effect of preservation at 4°C on the seminalepididymal attributes. The sperm concentration, total sperm output, progressive sperm motility, viability, HOS reactivity, and spermwith droplets decreased significantly (p
Keywords: Biometry; Buck; Epididymis; Slaughtered testis; Seminal attributes; Storage effect